E-Learning Related Attitudes, English Language Learning Strategies, And Academic Performance In English Of Grade 9 Students Of Divine Word College Of San Jose - Joy M. Ocampo, MAT, Hanna; D. Gorospe, EdD, Joanne (CV. Inara, 2022)
This study aimed to assess students’ academic performance in English by looking through their e-learning related attitudes and their English language learning strategies. Descriptive-correlational and descriptivepredictive research designs were used in this study. Respondents of the study were 150 Grade 9 students of who were enrolled in English 9 synchronous learning and were selected through probability sampling. Respondents’ attitude toward e-learning was measured using Test of E-learning Related Attitude (TeLRA) Scale and the extent of English language learning strategies of the students was measured using Strategy Inventory of Language Learning (SILL). Their academic performance in English was measured based on their quarterly grades in their English subject. Results of the study revealed that the students have neutral attitude toward e-learning and they use English language learning strategies such as affective, memory compensation, metacognitive, cognitive, and social strategies at a high extent. The students were found highly proficient in English. No significant relationship was found between and among e-learning related attitudes, English language learning strategies, and academic performance in English. Moreover, only metacognitive strategies best predicts academic performance and only challenges of e-learning best predicts the English language learning strategies of the students. This study concluded that e-learning attitude and English language strategies has nothing to do with students' academic performance in English.